Carers' views on autism and eating disorders comorbidity: qualitative study. Issue 3 (May 2020) - Adamson, James; Kinnaird, Emma; Glennon, Danielle; Oakley, Madeleine; Tchanturia, Kate
Abstract : Background: Patients with co-occurring anorexia nervosa and autism respond differently to eating disorder treatments. Previous interviews with patients with both conditions and clinicians working in eating disorder services has highlighted service and treatment adaptations might be beneficial and could improve outcomes for these individuals. Aims: The aim of this study was to explore carers' experiences of current treatment approaches for people with autism who have anorexia nervosa, and their views on how these can be improved. Method: Ten carers of a loved one diagnosed with autism and anorexia nervosa were interviewed using a semi-structured interview schedule and the transcripts were analysed with thematic analysis. Results: Four key themes emerged from the interviews: the role of autism in anorexia nervosa, carers' problems with clinical services, the impact on carers and suggestions for future improvements. Conclusions: Carers agreed that autism played a significant role in the development and maintenance of their daughters' anorexia nervosa. However, this comorbidity does not appear to be appropriately addressed in current treatment provisions. They described several difficulties, including problems getting an autism diagnosis and the perception that eating disorder services did not accept or adapt around the condition. This resulted in feelings of frustration and isolation for families, a scenario exacerbated by a perceived lack of support or specific resources for carers of individuals on the autism spectrum. Clinical recommendations on the basis of the current and previous studies are outlined.